-(7x+10)-10=-8(4+x)

Simple and best practice solution for -(7x+10)-10=-8(4+x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -(7x+10)-10=-8(4+x) equation:


Simplifying
-1(7x + 10) + -10 = -8(4 + x)

Reorder the terms:
-1(10 + 7x) + -10 = -8(4 + x)
(10 * -1 + 7x * -1) + -10 = -8(4 + x)
(-10 + -7x) + -10 = -8(4 + x)

Reorder the terms:
-10 + -10 + -7x = -8(4 + x)

Combine like terms: -10 + -10 = -20
-20 + -7x = -8(4 + x)
-20 + -7x = (4 * -8 + x * -8)
-20 + -7x = (-32 + -8x)

Solving
-20 + -7x = -32 + -8x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '8x' to each side of the equation.
-20 + -7x + 8x = -32 + -8x + 8x

Combine like terms: -7x + 8x = 1x
-20 + 1x = -32 + -8x + 8x

Combine like terms: -8x + 8x = 0
-20 + 1x = -32 + 0
-20 + 1x = -32

Add '20' to each side of the equation.
-20 + 20 + 1x = -32 + 20

Combine like terms: -20 + 20 = 0
0 + 1x = -32 + 20
1x = -32 + 20

Combine like terms: -32 + 20 = -12
1x = -12

Divide each side by '1'.
x = -12

Simplifying
x = -12

See similar equations:

| 2(c+6)=3G-6g | | x=3x-40 | | 7b=10b+18 | | 6(-10p-3)-8p=6(-12p-3)-4 | | v^2-4v-37=2 | | 24x-3(2x-5)=51 | | 73-x=86-2x | | (2x^2-3xy^2-y^2)-(3x^2-xy^2)= | | F(X)=20(0.9)x^6 | | 6m+9+7x-2= | | 9.25x=5.75x+40 | | 8w-12=(-4) | | -10+6m-m=-1+3m+5m | | 74t+28t-101t+16=89 | | 3n-6=3-5n-n | | 5+7-9-8=11 | | -4(w+1)=-20 | | -7y+14=-28 | | 5x^2+4x=-3 | | 4x-10=3x-4 | | -540+13p=1500 | | -67a+56a=99 | | 4n^2=256 | | 4x-30=130 | | 37a-73a+73a+-33a=100 | | -2a-2=0 | | 5x-5.5=5x+26 | | x^2y+2xy-4x+y=0 | | 9c+13=58 | | 3x-4=-6x+14 | | 180-(x+50)=x+10 | | 9x+5-2x+1=27 |

Equations solver categories